Tyrosine 146 of the Human Na+/Taurocholate Cotransporting Polypeptide (NTCP) Is Essential for Its Hepatitis B Virus (HBV) Receptor Function and HBV Entry into Hepatocytes - Dariusz Zakrzewicz; Regina Leidolf; Sebastian Kunz; Simon Franz Müller; Anita Neubauer; Silke Leiting; Nora Goldmann; Felix Lehmann; Dieter Glebe; Joachim Geyer (Viruses, 2022)
Na+/taurocholate cotransporting polypeptide (NTCP, gene symbol SLC10A1) is a hepatic bile acid uptake carrier participating in the enterohepatic circulation of bile acids. Apart from its transporter function, NTCP acts as the high-affinity liver-specific receptor for the hepatitis B virus (HBV), which attaches via its preS1-peptide domain of the large surface protein to NTCP, subsequently leading to endocytosis of the virus/NTCP-receptor complex. Although the process of NTCP-dependent HBV infection of hepatocytes has received much attention over the last decade, the precise molecular sites of the virus/NTCP interaction have not been fully identified. Inspection of the primary protein sequence of human NTCP revealed 139YIYSRGIY146 as a highly conserved tyrosine-rich motif. To study the role of Y139, Y141 and Y146 amino acids in NTCP biology, the aforementioned residues were substituted with alanine, phenylalanine or glutamate (mimicking phosphorylation) using site-directed mutagenesis. Similar to wt NTCP, the Y139A, Y141A, Y146A, Y141F, Y146F, and Y146E mutants were expressed at the plasma membrane of HEK293 cells and exhibited intact bile acid transport function. Y146A, Y146E, and Y146F demonstrated transport kinetics comparable to wild-type NTCP with Km values of 57.3–112.4 µM and Vmax values of 6683–7579 pmol/mg protein/min. Only Y141E was transport deficient, most likely due to an intracellular accumulation of the mutant protein. Most importantly, Y146A and Y146E mutation completely abrogated binding of the viral preS1-peptide to NTCP, while the Y146F mutant of NTCP showed some residual binding competence for preS1. Consequently, the NTCP mutants Y146A and Y146E, when expressed in HepG2 hepatoma cells, showed complete loss of susceptibility for in vitro HBV infection. In conclusion, tyrosine 146, and to some extent tyrosine 141, both belonging to the tyrosine-rich motif 139YIYSRGIY146 of human NTCP, are newly identified amino acid residues that play an essential role in the interaction of HBV with its receptor NTCP and, thus, in the process of virus entry into hepatocytes.